Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025712
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Digital Creativity Support To Improve Health-and-Safety in a Manufacturing Plant

Abstract: This paper reports an evaluation of digital support for human creativity to improve health-and-safety in one manufacturing plant. It reports the use of this support as part of the plant's risk management process over 66 working days. Results revealed that this use led to more complete, more useful and more novel risk resolutions, compared with the original paper process, and informed how digital creativity support can be rolled out across manufacturing plants, as well as to other domains not recognized as crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…These qualities of novelty and value mapped to the requirements for news to be surprising and relevant revealed during a review of key qualities of news reported in 2016 [32]. It also investigated whether: (RQ3) factors such as increased newsroom autonomy, a work culture open to innovation, management support to train journalists and set up success conditions and the presence of innovative individuals [30] influenced the use and the effectiveness of the INJECT tool.…”
Section: Figure 3 the Inject Web Application Version Providing Creatmentioning
confidence: 99%
See 1 more Smart Citation
“…These qualities of novelty and value mapped to the requirements for news to be surprising and relevant revealed during a review of key qualities of news reported in 2016 [32]. It also investigated whether: (RQ3) factors such as increased newsroom autonomy, a work culture open to innovation, management support to train journalists and set up success conditions and the presence of innovative individuals [30] influenced the use and the effectiveness of the INJECT tool.…”
Section: Figure 3 the Inject Web Application Version Providing Creatmentioning
confidence: 99%
“…Indeed, the results revealed that the use of INJECT sometimes decreased journalist productivity. The evaluated design did not provide journalists with the simultaneous creativity and productivity gains obtained by professional users in domains such as manufacturing [30]. Unlike INJECT, this other tool automatically generated new creative content that the users could adapt more quickly than generate and write themselves.…”
Section: Wider Implications For Digital Creatvity Support In Journalismmentioning
confidence: 99%
“…The plant employees documented 370 new risk descriptions and resolutions with the application in the deployment period. Compared to the first period [14], however, the mean numbers of words reported in Table 1 to describe each risk (7.8 to 15.2) and resolution (11.2 to 29.8) were both lower, the mean time to describe a risk and resolution was higher (6m44s to 4m46s), and the percentage (52.2%) of risk resolutions completed within the 5-minute constraint was lower. Indeed, the distribution of the total numbers of risks resolved within each one-minute period, depicted graphically in Figure 3, revealed that many risks took more than 10 minutes to resolve, and 8 required more than 30 minutes.…”
Section: Autumn 2015 To Summer 2016: Adapting For the Uk Plantmentioning
confidence: 81%
“…No major usability problems were reported. A rigorous comparison of these 115 risk resolutions to a similar number of risk resolutions documented by the same employees 12 months earlier with the paper forms, and reported at length in [14], revealed that the risk resolutions documented with the application were rated by risk analysts to be both more novel and more useful. Unlike with the paper forms, use of the application was associated with all risks having documented resolutions, and these resolutions were documented with more words than the ones on the forms.…”
Section: The Spring Of 2015: Deployment In First Plantmentioning
confidence: 96%
See 1 more Smart Citation